Implementation of an Integrated Stunting Monitoring System: A 7-Day Intervention Study - A V, Kartika; S, Latief; S, Darma; A R, Bamahry (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives. Stunting is one of a problem faced in Indonesia. Based on The Indonesian Nutrition Status Survey (SSGI) in 2022, stunting prevalence in Indonesia reached 21.6%, two percent higher compared to WHO’s requirement. To overcome the problem, our government carried out several stunting management programs. Unfortunately, the results weren’t optimal. Based on this, we propose an integrated stunting monitoring system involving hospitals, educational institutions, government, and food producing business which considered to be able to speed up the treatment of stunting patients. Methods. There were four children aged 2-3 years who were diagnosed with stunting through screening examinations by a paediatrician. The nutrition given to each child is calculated based on the value of daily nutritional needs by a nutritionist. The diets were prepared by a professional chef working at a restaurant. All menus were distributed by the government staff. Evaluation of nutritional intake is carried out every day by a medical student. Changes in body weight were measured using body weight scale on day seven. Data were analysed with paired T-test using IBM SPSS Statistics 26.0. Results. The results showed that all respondents' weight increased by up to 150 grams after receiving intervention in the form of measured nutritional intake. During the monitoring period, the child’s eating patterns experienced significant improvements. Children received a more balanced diet with more complete nutrition. Conclusion. This research provides initial evidence that integrated monitoring of the provision of measured nutritional intake is indeed effective. Applying the intervention to a bigger sample with longer observation period will provide stronger evidence for its efficacy and efficiency. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S65